Pengembangan Instrumen Penilaian Kinerja Peserta Didik Pada Praktikum Larutan Elektrolit dan Nonelektrolit Kelas X SMA di Kecamatan Sambas - Sri Nurabmi; Eny Enawaty; Ira Lestari (Universitas Muhammadiyah Pontianak, 2021)
This study aimed to determine the level of feasibility and response of chemistry teachers to students' performance appraisal instruments on practicum electrolyte and non-electrolyte solutions that have been developed. The research method used is Research and Development (R&D) by the Borg and Gall model. This study’s subject was the instrument of student performance appraisal, which was tested on chemistry teachers in Senior High School, Sambas. The instrument of student performance appraisal on the electrolyte and non-electrolyte solution practicum that has been developed shows that the category is very feasible with a percentage of 87.31% in terms of three aspect of the assessment feasibility content, presentation, and language. The chemistry teacher's response to the student performance appraisal instrument in the initial field test showed an excellent category (80.55%). In the main field test, the category showed excellent (85.83%). The results of this study indicate that the instrument of student performance appraisal in practicum electrolyte and non-electrolyte solutions is very feasible and can be used as one of the assessment tools in the chemical practicum of electrolyte and non-electrolyte solution materials.